Does audit quality matters in Malaysian public sector auditing? / Aida Hazlin Ismail... [et al.] - Ismail, Aida Hazlin; Muhammad Merejok, Natasha; Mat Dangi, Muhamad Ridhuan; Saad, Shukriah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Auditors play a key role in contributing to the credibility of the financial statements on which they are reporting. High-quality audits support financial stability. The responsibility for performing quality audits of financial statements rests with the auditors. However, audit quality is best achieved in an environment where there is support from and appropriate interactions among participants in the financial reporting supply chain. Most prior studies look into audit quality from the perspective of private sector however this study focus on the quality of public sector auditing in Malaysia. There are three independent variables being investigated in this study that are the auditor’s independence, auditor’s competency and auditor’s workload. Data were collected through the distribution of questionnaires to 114 samples of auditors involved in public sector audit in Malaysia. The data were analysed using correlation test and regression test. The findings of this study show that there are positively significant relationship between auditor’s independence and auditor’s competency on audit quality. The results revealed that auditor’s competency is the most significant factor affecting the audit quality in public sector audit. However, results show that auditor’s workload has a negative and insignificant impact on audit quality. Hence, this study recommends that the audit departments to strengthen the audit quality and could improve the quality of the financial reporting in the public sector. In addition, auditor’s competency should be enhanced among the auditors in public sector to ensure high quality of audit work performed. Future studies should explore other variables such as client satisfaction, auditor switching and auditor’s turnover in public sector auditing.